2006
DOI: 10.1242/jeb.02338
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to different thermal conditions in a northerly wintering shorebird is driven by body mass-related changes in organ size

Abstract: There was an error published in J. Exp. Biol. 209,[3141][3142][3143][3144][3145][3146][3147][3148][3149][3150][3151][3152][3153][3154] In paragraph 4 of the Respirometry section of the Materials and methods, the authors stated: Therefore, energy consumption was estimated using a constant equivalent of 20·kJ·l -1 O 2 and then converted to watts using 1·W=0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 93 publications
(136 reference statements)
11
109
5
Order By: Relevance
“…The thermogenic aerobic scope of tropical birds, fAS C , was not related to M b , which may be an effect of the small range in M b of 9.6-71, and averaged 4.5 ϫ BMR or 15-34% lower than fAS E (Table 1). fAS C was 22% lower in tropical birds than in temperate birds (20): a significant difference despite extensive overlap with values reported for temperate bird species that fall within the range of 3-9 ϫ BMR (6,23,45).…”
Section: Discussionmentioning
confidence: 57%
“…The thermogenic aerobic scope of tropical birds, fAS C , was not related to M b , which may be an effect of the small range in M b of 9.6-71, and averaged 4.5 ϫ BMR or 15-34% lower than fAS E (Table 1). fAS C was 22% lower in tropical birds than in temperate birds (20): a significant difference despite extensive overlap with values reported for temperate bird species that fall within the range of 3-9 ϫ BMR (6,23,45).…”
Section: Discussionmentioning
confidence: 57%
“…Wiersma and colleagues found that Panamanian birds have lower maximal metabolic rates than temperate birds during forced exercise and shivering thermogenesis, as well as lower BMR (Wiersma et al 2007a). They suggested that the reduced aerobic capacity might derive from lower demands for flight performance in tropical forests, where most birds are nonmigratory and many are relatively sedentary; this, as well as low BMR (Vezina et al 2006;Daan et al 1990;Chappell et al 1999) is consistent with data in tropical species showing relatively small organ masses (pectoral muscle, heart, lung, liver, kidney, liver, pancreas; Wiersma et al…”
Section: Discussionmentioning
confidence: 99%
“…Following a 1-month health quarantine period, the birds were randomly assigned to one of three identical outdoor aviaries on 27 October 2009. The birds were exposed to the local ambient temperature and photoperiod at 51°N, but sheltered from wind and precipitation (for aviary details, see Vézina et al 2006). The mean (± SE) monthly temperatures during the trial period were 9.6 ± 0.…”
Section: Methodsmentioning
confidence: 99%
“…The first respirometry trial was conducted on 23 November 2009, 27 days after the birds were established in outside aviaries. We measured oxygen consumption (V O 2 ) and calculated metabolic rates using a flow-through respirometry system on ≤4 individuals per trial (for setup details, see Vézina et al 2006).…”
Section: Methodsmentioning
confidence: 99%